Plasma Lipoprotein Particle Subclasses in Preterm Infants - Scoble, Jennifer A.; Smilowitz, Jennifer T.; Argov-Argaman, Nurit; German, J. Bruce; Underwood, Mark A. (American Journal of Perinatology, 2018)
Objective A pilot study to determine lipoprotein classes and subclasses in premature infants and examine associations with nutritional intake, gestational age (GA), and morbidity.Study Design Plasma lipoprotein particle concentrations were analyzed in a cohort of 15 premature infants in the first 5 days of life and again at 2 weeks. Breast milk samples were analyzed for fatty acid content. Associations between lipoprotein particle subclasses and GA, breast milk intake, milk fatty acid intake, and chronic lung disease (CLD) were determined.Results At 2 weeks of age, more premature infants had higher concentrations of total very low-density lipoprotein and lower concentrations of total high-density lipoprotein (HDL) and large HDL particles (similar to profiles seen in adults and children with infectious disease, cardiometabolic disease, and diabetes). Lower total HDL, large HDL, and medium HDL and a higher small HDL:total HDL ratio at 2 weeks were each associated with CLD with GA a likely confounder. Intake of human milk C18 and C20 fatty acids was inversely correlated with plasma total LDL concentration at 2 weeks of age.Conclusion Dyslipidemia was common in extremely premature infants and was associated with CLD and with lower intake of specific long chain fatty acids.
Keywords: high-density lipoprotein; low-density lipoprotein; very low-density lipoprotein; chronic lung disease; human milk; premature infant; fatty acid